Revealing New Prospects: Antipsychotic Drugs Induces Anti-tumor Effects against Gastric Cancer through Inducing Apoptosis - Amjadi, Omolbanin; Hedayatizadeh-Omran, Akbar; Zaboli, Ehsan; Janbabaei, Ghasem; Lira, Sergio A; Ahangari, Ghasem (Current cancer drug targets, 2025)
Globally, Gastric Cancer (GC) ranks as the fifth leading cause of cancer-related deaths. GC is a multifaceted malignancy with diverse etiologies; however, understanding the shared molecular mechanisms can aid in discovering novel targeted therapies for GC. This study has employed a drug repositioning approach to explore new drug candidates for treating GC. The human GC cell lines AGS, MKN-45, and KATO-III were treated with different concentrations of dopamine, cabergoline, thioridazine, and entacapone to determine effective doses and IC50 values. , cytotoxic activity on cancer cell lines was screened based on dose/time using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Quantitative Reverse Transcriptase Polymerase Chain Reaction (qRT-PCR) was used to measure the mRNA expression of B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein (Bax), and Proliferating Cell Nuclear Antigen (PCNA) in each group. The percentage of apoptotic cells was evaluated using Annexin V/PI staining. Dopamine, cabergoline, thioridazine, and entacapone elicited cytotoxic effects on AGS and KATO-III cells in a dose-dependent manner and elevated the percentage of Annexin Vpositive cells, suggesting the occurrence of apoptosis. The expression of Bcl-2 and PCNA was significantly decreased, whereas the expression of Bax was considerably increased in the AGS and KATO-III cells compared to that in the blank group (p < 0.05); however, no similar effect was observed in MKN-45 cells. Through experiments, this study provides evidence that the antipsychotic drugs cabergoline, dopamine, thioridazine, and entacapone can inhibit gastric cancer growth in AGS and KATO-III cells. These findings suggest that these drugs could be repurposed as novel therapeutic agents for the treatment of gastric cancer.